A Comparative Study on the Cultural Communication Paths and Effectiveness of Chinese and Western Health and Wellness Models in the Context of the Guangdong-Hong Kong-Macao Greater Bay Area - Sun, Jingwen; Wang, Xiya (Pinnacle Academic Press Proceedings Series, 2026)
This paper explores the cultural dissemination paths and comparative effectiveness of the traditional Chinese health maintenance model and Western wellness practices within the context of the Guangdong-Hong Kong-Macao Greater Bay Area. Drawing on the region’s high degree of mobility, cultural diversity, and policy support for health industries, the study examines how these two models are introduced, communicated, and localized among different social groups. Particular attention is paid to their distinct philosophical foundations, including holistic and preventive orientations in Chinese health maintenance and individual-centered, lifestyle-oriented approaches in Western wellness. The analysis further considers media channels, institutional promotion, commercial platforms, and interpersonal networks as key vectors of cultural transmission. By integrating perspectives from cultural studies, public health, and communication studies, the paper evaluates how values, beliefs, and social norms shape the reception and practice of these health models. It also assesses their perceived effectiveness in promoting physical health, psychological well-being, and longevity across communities in the Greater Bay Area. Finally, the study discusses opportunities and challenges in fostering mutual learning and hybrid practices, and reflects on the implications for regional health governance, cultural integration, and the development of innovative health and wellness services.